2011
DOI: 10.3109/02770903.2011.608458
|View full text |Cite
|
Sign up to set email alerts
|

Atopy Is Associated with Asthma in Adults Living in Rural and Urban Southwestern Nigeria

Abstract: Atopy is associated with adult asthma in southwest Nigeria. Larger studies to confirm the nature of this association and to examine the role of helminthic infection and other environmental factors on the expression of asthma are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Overall, the factors that determine asthma in African communities remain controversial with conflicting reports about the role of atopy and parasitic infestations [31,32]. Atopy does not fully explain the distribution of asthma in urban and rural African communities, neither does parasitic load clearly define the divide between asthma in rural and urban communities in Nigeria [25,33]. As in many previous reports on the influence of gender on asthma prevalence and severity, we found that older women tend to report more asthma symptoms than men compared with younger age groups.…”
Section: Discussionmentioning
confidence: 97%
“…Overall, the factors that determine asthma in African communities remain controversial with conflicting reports about the role of atopy and parasitic infestations [31,32]. Atopy does not fully explain the distribution of asthma in urban and rural African communities, neither does parasitic load clearly define the divide between asthma in rural and urban communities in Nigeria [25,33]. As in many previous reports on the influence of gender on asthma prevalence and severity, we found that older women tend to report more asthma symptoms than men compared with younger age groups.…”
Section: Discussionmentioning
confidence: 97%
“…This may have resulted in wide confidence intervals and thus reduced power to detect a statistically significant difference. Some studies had small sample sizes and are likely to have been underpowered . Although the prevalence of SPT was generally higher in many investigations, its association with helminths was not consistent for reasons that are not well understood.…”
Section: Helminths and Reported Or Diagnosed Allergy‐related Outcomesmentioning
confidence: 99%
“…Serum samples were frozen and stored at -80 0 C until analysis was performed. Samples were analyzed for white blood cells, IgE, hemoglobin phenotype, eosinophils and G6PD status as previously described 14 .…”
Section: Blood Samplementioning
confidence: 99%
“…Allergy skin testing Allergy skin test was performed using the Skintestor OMNI TM (Greer Laboratories, Inc., Lenoir, North Carolina) on the volar side of the forearm with standardized extracts of eight groups of allergens as we previously described 14 . Skin response was measured after 15 minutes, considering skin wheal diameter.…”
Section: Blood Samplementioning
confidence: 99%
See 1 more Smart Citation